Unilateral focal choroidal excavation in autosomal recessive bestrophinopathy - Neha Goel (Journal of Clinical Ophthalmology and Research)
Focal choroidal excavation (FCE) refers to one or more areas of localized choroidal excavation seen on spectral-domain optical coherence tomography, in the absence of a posterior staphyloma or scleral ectasia. A case of unilateral FCE in a 17-year-old male with autosomal recessive bestrophinopathy (ARB) is described with multimodal imaging findings. ARB is a rare inherited retinal dystrophy resulting from mutations in the BEST1 gene. We present the clinical and imaging findings of this unusual association.